PERAN MODAL SOSIAL DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA PERSPEKTIF MAQASHID SYARIAH (STUDI KASUS YAYASAN ROMBONG SEDEKAH JOMBANG) - Sakethi Arrow Rulloh Saher; Irham Zaki (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This research is aimed to figure out and explain the role of social capital by seing from the correlation of networks, norm, and belief to improve the welfare of the community with maqashid syariah indicator. Qualitative research method and case study were used in this research as the strategy. This research possess an unit analysisof social capital and the improvement of social welfare which receive a loan with free riba from Rombong Sedekah Fondation. The data was collected by interviewing and observing to the direct object of the research. This research is interviewing staff on Rombong Sedekah Jombang Foundation andpeople who get donations from foundation. The qualitative explanatory was used as the techniques of analysis by explaining the results of the interviewers and of the direct observation. The result reveals that social capital with norms. Networks, and belief play a important role to improve the social welfare by seeing from maqashid syariah. REFERENCESAgustin, Atut Frida dkk. 2013. Identifikasi Modal Sosial Pada Program       Pemberdayaan Masyarakat Miskin Melalui Dana Zakat, Infaq dan Sedekah. IQTISHODUNA, Vol.  9, No : 1-8.Bourdieu, Pierre. 1990. The logic of Practice. Atandford University Press: California. Hal: 54Bungin, Burhan. 2003. Analisis Data Penelitian Kualitatif: Pemahaman Filosofis dan Metodologis ke Arah Penguasaan Model Aplikasi. Jakarta: PT. Raja Grafindo PersadaCahyono, Ardian. 2012. Peran Modal Sosial Dalam Peningkatan Kesejahteraan Masyarakat Petani Tembakau di Kabupaten Wonosobo. UNISSULA, Vol. 1, No. 1, Desember: 131-144.Field, John. 2010. Modal Sosial. Bantul: Kreasi Wacana.Fu, Qianhong. 2004. Trust, Social Capital, and Organizational Effectiveness.Faculty of the Virginia Polytechnic Institute and State University, 22 April: 1-34.Fukuyama, Francis. Trust: Kebijakan Sosial dan Penciptaan Kemakmuran. 2002. Yogyakarta: CV. Qalam Yogyakarta.Furbey, Robert, et al. 2006. Faith as social capital. Sheffield Hallam University, Maret: 1-61.Handoyo, Eko. 2013. Kontribusi Modal Sosial Dalam Meningkatkan Kesejahteraan Pedagang Kaki Lima Pascarelokasi. Jurnal UNNES, Jurnal Komunitas 5 (2) (2013): 252-266Hasbullah, Jousairi. 2006. Social Capital: Menuju Keunggulan Budaya Manusia. Indonesia. Jakarta: MR- United Press.Kara, Muslimin. 2012. Pemikiran Al-Syatibi Tentang Maslahah dan Implementasinya Dalam Pengembangan Ekonomi Syariah. ASSETS, Vol. 2 No. 2, 2012: 173- 184Kearns, Ade. 2004. Social Capital, Regeneration & Urban Policy. CNR PaperVol.15, April 2004:1-39Mahalli, Ahmad Mudjab dan Ahmad Rodli Hasbullah. 2004. Hadist-hadist Muttafaq ‘Alaih: Bagian Munakahat dan Mu’amalat. Jakarta: Prenada Media Group.Mulyono,Sutrisno Purwohadi. Bentuk-Bentuk Penerapan Norma Hukum Adat Dalam Kehidupan Masyarakat Di Jawa Tengah. Jurnal Media Hukum, Edisi 252.Muflikhati, dkk. 2010. Kondisi Sosial Ekonomi dan Tingkat Kesejahteraan Keluarga: Kasus di Wilayah Pesisisr Jawa Barat.Jurnal Ilm. & Kons, vol 3, No 1Nasution, dkk. 2014. Dampak Modal Sosial Terhadap Kesejahteraan Rumah Tangga Pedesaan di Indonesia. MIMBAR, Vol.30, No.2, Desember: 137-148.Piere Bourdeiau. 1990. The Logic of Practice. Atanford University Presss: California, Hal:54Pusparini, Dwi Martini. 2015.  Konsep Kesejahteraan Dalam Ekonomi Islam: Perspektif Maqasid Asy-Syari’ah. Jurnal UII Yogyakarta, Vol.1 No.1, Juni: 45-59.Rahmawati, lilik. 2012. Konsep Ekonomi Al-Ghazali. Maliyah. Vol.2, No. 1, Juni: 329-341.Sampe, Evi, dkk. Pengembangan Jejaring Organisasi Yayasan Sangatta Baru (YSB) untuk Meningkatkan Kesejahteraan Sosial Masyarakat. Jurnal Administrasi Publik, Vo;. 2, No. 3: 471- 477.Sanrego, Yulizar D, dan Moch. Taufiq. 2016. Fiqih Tamkin (Fikih Pemberdayaan). Jakarta: Qisthi Press.Simamora, Sogar. 2012. Karateristik, Pengelolaan, dan Pemeriksaan Badan Hukum Yayasan di Indonesia. Jurnal Rechts Vinding, Vol. 1, No. 2, Agustus: 175-186.Sodiq, Amirus. 2015. Konsep Kesejahteraan Dalam Islam. EQUILIBRIUM, Vol. 3, No.2, Desember.Somantri, Gumilar Rusliwa. Memahami Metode Kualitatif. 2005. MAKARA, SOSIAL HUMANIORA, VOL. 9, NO. 2,Suarez, Christoper. 2005. Civil Society adn the Dangers of Social Capital. Vol. 1, 18 Maret, 2005: 1-10.Syahra, Rusydi. 2003. Modal Sosial: Konsep dan Aplikasi. Jurnal Masyarakat dan Budaya, Vol. 5, No. 1: 1-20.Siisiäinen, Marti. 2000. Two Concepts of Social Capital: Capital: Bourdieu vs. Putnam. Jurnal dipresentasikan pada Konferensi Internasional ISTR yang keempat "The Third Sector: For What and for Whom?".Trinity College, Dublin, Ireland : July 5-8, 2000http://nasional.news.viva.co.id/news/read/583838-empat-pns-jadi-tersangka-korupsi-dana-zakat. Diakses pada tanggal 07 April, 2017, pukul 01.23 WIB.Widayani, Retno, & Rachman. 2013. Studi Tentang Kemunculan Modal Sosial. Jurnal Kebijakan dan Administrasi Publik, Vol. 17, No. 2: 65-75.